Perbaikan Postur Kerja untuk Mencegah Cedera Kerja di CV Cahaya Setia Mulia Abadi - Egga Jerri Indri Saputri; Widya Setiafindari (Jurnal Kendali Teknik dan Sains, 2025)
Sewing workers at CV Cahaya Setia Mulia Abadi perform static and repetitive tasks, such as prolonged sitting in a bent posture and continuous sewing movements. These conditions lead to various physical complaints, including back pain (78%), lower neck pain (75%), upper neck discomfort (73%), as well as shoulder fatigue, wrist tingling, and lower back stiffness. This research is conducted to evaluate the potential risk of musculoskeletal disorders (MSDs) through the application of the Rapid Entire Body Assessment (REBA) method, determine the body parts most frequently affected using the Nordic Body Map (NBM) questionnaire, and develop posture correction strategies based on anthropometric measurements.The REBA results indicate that most sewing activities fall into the medium-risk category (score 5–7), with some in the high-risk category (score 8). The intervention involved adjusting chair dimensions based on anthropometry, and adding seat cushions and backrests. After the simulation of improvements, the REBA score decreased to 2, placing it in the low-risk category. These findings demonstrate that ergonomic chair design and proper working posture significantly reduce physical strain, increase comfort, and help maintain worker productivity. This study offers practical recommendations for creating a healthier and safer work environment in the manufacturing sector.